THE INFLUENCE OF ENVIRONMENTAL SOCIAL GOVERNANCE (ESG) DISCLOSURE, LIQUIDITY, LEVERAGE, AND ACTIVITY ON FIRM VALUE - Yosita Kartika; Amir Indrabudiman (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure, liquidity, Leverage, and activity on firm value in technology sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Firm value is measured using Price to Book Value (PBV), while liquidity by Current Ratio (CR), Leverage by Debt to Assets Ratio (DAR), and activity by Total Assets Turnover (TATO). This study employs a quantitative approach using purposive sampling to select the sample firms. The data are analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 27, preceded by descriptive statistical analysis and classical assumption tests. The results indicate that ESG disclosure, liquidity, and Leverage have a significant effect on firm value, while activity do not have a significant effect. The findings of this study are expected to contribute to the development of financial accounting literature and provide practical insights for corporate management and investors in making informed investment decisions, particularly in the technology sector.